ARANG DAN CUKA KAYU PRODUK HASIL HUTAN BUKAN KAYU UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN DAN SERAPAN HARA KARBON - Sri Komarayati; Gusmailina; Gustan Pari (BRIN Publishing, 2013)
Charcoal and wood vinegar exert significant role as carbon sources yielded from the carbonization process, and afford multi benefits in their use for enhancing plant growth and stimulating carbon nutrient absorption. In relevant, this scientific narration presents results of trial tests employing charcoal and wood vinegar on the growth media for sprouts of sengon, jabon and agarwood producing plants, which lasted for 6 months at the planting experiment site. This experiment aimed to scrutinize the growth responses of such plant sprout species; and the examine the contents of carbon, nitrogen, phosphor, potassium in the soil and in plant biomass after being added with charcoal and wood vinegar. Charcoal addition proceeded by mixing it with soil evenly, while wood vinegar addition was done by showering it on to the soil. Nurturing of plants took place by spraying wood vinegar on their stems, branches, twigs and leaves. Results revealed that the additions of charcoal and wood vinegar on the growter media for sengon sprouts increased as much as 127-208% in beight and 109-129% in diameter of the corresponding sengon plants. For jabon plants, the addition of charcoal and wood vinegar brought about in increase 117-142% as much in their beight, and 166-128% in their diameter. Meanwhile, for eaglewood producing plants there appeared still no significant growth effect attributed by such addition, since it seemingly took considerable time for them to adapt themselves. Further, the incorporation of charcoal and wood vinegar brought about an increase of carbon nutrient adsorption in the soil and biomass. Besides carbon (C), adsorption of N, P, and K nutrients also increased.